2010
DOI: 10.1007/s11595-010-0049-4
|View full text |Cite
|
Sign up to set email alerts
|

High-g impact resistance for epoxy molding compound

Abstract: The behavior of resistance high-g impact of EMC (epoxy molding compound) with two package models, small outline package (POS) and Globtop, was evaluated by experimental method used Hopkinson bar. At 120,000 g (generated in the Hopkinson bar with widths about 70 μs) no damage in either the POS devices or the Globtop devices was observed. In order to enhance the EMC's ability of resistance high-g impact, buffering effect of epoxy resin was also studied. The experimental results above all show that EMC has a bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Based on pyrolysis products analysis and the bond energy theory, the pyrolysis mechanisms of organics in EMC were proposed, as shown in Figure . For thermal-instable ingredients, the pyrolysis process of polymers is composed of a series of free radical reactions based on fracture and combination of chemical bonds initiated by energy provided by the reaction system. , First, scission of the main chain and the fracture of C–CH 3 bonds occurred due to the fractures of chemical bonds with lower bond energies. The derived methyl groups played an important role in later reactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on pyrolysis products analysis and the bond energy theory, the pyrolysis mechanisms of organics in EMC were proposed, as shown in Figure . For thermal-instable ingredients, the pyrolysis process of polymers is composed of a series of free radical reactions based on fracture and combination of chemical bonds initiated by energy provided by the reaction system. , First, scission of the main chain and the fracture of C–CH 3 bonds occurred due to the fractures of chemical bonds with lower bond energies. The derived methyl groups played an important role in later reactions.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 10 mg of the samples of raw material was heated from 30 to 900 °C at three constant rates (10, 20, and 30 °C/min) under an argon flow of 50 mL/min. The apparent activation energy was calculated based on the Flynn–Wall–Ozawa equation expressed as eq . where β is the heating rate, g (α) is the integrated form of the conversion dependence function, R is the mol gas constant (8.314 J/mol·K), T is the thermodynamic temperature, and E is the apparent activation energy. The activation energy can be determined by the slope of linear function plot of log β versus 1/ T at given value of the conversion.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have also attempted to composite other carbon materials to improve material properties. Jin 75 composited ZIF-8 crystals with carbon paper (CP) by hydrothermal method and successfully prepared ZIF-8/CP-CH 3 OH composites at different hydrothermal temperatures to study the effects of hydrothermal temperatures on the desalination amount and desalination efficiency of the ZIF-8/CP-CH 3 OH composites. Results revealed that the loading of carbonized MOFs would greatly improve the desalination capacity and desalination efficiency of CP.…”
Section: Zif-8 Derived Carbon As CDI Electrode Materialsmentioning
confidence: 99%
“…In addition, the diameter of these holes is consistent with the size of ASA particles, 24 which further proves this point. However, with the incorporation of SBS, the SBS phase is obvious on the cryo-fractured surfaces because of the poor miscibility between SBS and PVC, 25 and its size increases with the increasing SBS content, which can preliminarily judge that ASA and SBS are dispersed in the PVC matrix. After surface etching by toluene, the cryo-fractured surface of the neat PVC is still flat.…”
Section: Prediction and Verification Of The Phase Morphology Of Ternamentioning
confidence: 99%